Running to Freedom: The Flight of the Fathers of Illegitimate Children to the Colonies of the British Empire, 1875-1901 - Florence Pellegry (Cahiers Victoriens et Edouardiens)
Through the close study of private correspondence extracts and first-hand testimonies found in the London Foundling Hospital archives, this paper will analyse the phenomenon of the flight towards the colonies of the British Empire in the last quarter of the nineteenth century. In the archives of this charitable institute dedicated to the reception of abandoned and illegitimate children since 1739, distant southern colonies such as Australia, New Zealand, Southern Africa, but also India are omnipresent through recurrent references to the attempted flight of the fathers of illegitimate children. These remote places came to represent the possibility of starting over, of erasing one’s mistakes but also and most especially, in our case study, of distancing oneself from the mother of one’s illegitimate child and the related unwanted responsibilities. Through an examination of the correspondence between the men and the pregnant women they are abandoning, this paper will strive to better understand the conditions under which they chose to depart and the reasons why they did so in such an abrupt manner, ultimately focusing on male attitudes and behaviour regarding illegitimacy in late Victorian Britain.